KEMAMPUAN PENGUASAAN KONSEP BAHASA INDONESIA MAHASISWA PRODI PGMI STIT MUHAMMADIYAH TEMPURREJO NGAWI - Azharin, Barrin Putra (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2022)
PGMI study program equips the professional competencies of students through several courses of expertise, among others: Indonesian MI-I and II. With this course, it is expected that students already have the ability to conduct the learning process Indonesian by mastering these three concepts with breadth and depth. Based on preliminary research obtained data that mastery of the concept of Indonesian pgmi study program students are still in the low category. In addition, they also have some difficulty in learning these concepts. Based on the background of these problems, there are several problems that want to be answered in this study, namely: how the ability to master the concept of Indonesian pgmi study students, what difficulties faced pgmi students in mastering the concept of Indonesian, and how the efforts of PGMI majors in various research results mastering concepts and material difficulties Indonesian to improve the competence of PGMI students. The method used in this study is a qualitative descriptive method with case study design. The data collection techniques and instruments used are concept mastery tests with test questions, and interview techniques using structured interview guidelines and documentation studies. Data processing is analyzed simply with a percentage formula. The results showed that the level of mastery of the concept of Indonesian concept was in the good category. While the difficulties faced in all three areas are the lack of direct practice and media in studying theory. Therefore, PGMI study program will follow up the results of this study with curriculum and learning improvements.